2018
DOI: 10.1038/s41598-018-35031-0
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric Ixodes-tick species: pattern of distribution and pathogen transmission within wild rodent populations

Abstract: The generalist tick Ixodes ricinus is the most important vector for tick-borne pathogens (TBP), including Borrelia burgdorferi sensu lato, in Europe. However, the involvement of other sympatric Ixodes ticks, such as the specialist vole tick I. trianguliceps, in the enzootic circulations of TBP remains unclear. We studied the distribution of I. ricinus and I. trianguliceps in Central Finland and estimated the TBP infection likelihood in the most common rodent host in relation with the abundance of the two tick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…Consequently, a lower local extinction probability of their parasites (including small mammal specialist tick species like I. trianguliceps and I. acuminatus), and of the infectious agents they could transmit is expected (H1). (Agoulon et al 2012;Li et al 2012;Cayol et al 2018). However, in previous studies, no relationship was observed between the abundance of I. ricinus nymphs and B. burgdorferi s.l.…”
Section: Prevalence Of Anaplasma Phagocytophilummentioning
confidence: 87%
“…Consequently, a lower local extinction probability of their parasites (including small mammal specialist tick species like I. trianguliceps and I. acuminatus), and of the infectious agents they could transmit is expected (H1). (Agoulon et al 2012;Li et al 2012;Cayol et al 2018). However, in previous studies, no relationship was observed between the abundance of I. ricinus nymphs and B. burgdorferi s.l.…”
Section: Prevalence Of Anaplasma Phagocytophilummentioning
confidence: 87%
“…An alternative explanation for this non-linear association might be that I. ricinus is not a main vector of this parasite. Previous studies proposed I. trianguliceps, a nidicolous rodent tick species as the main vector [63][64][65]. It indicates that B. microti circulates in the, so called 'cryptic cycle' between specialist ticks and rodents, while I. ricinus sporadically becomes infected and perhaps acts as an occasional bridge vector to other host species [63].…”
Section: Rodent Density Versus Pathogens Amplified By Rodentsmentioning
confidence: 98%
“…in Europe. This is because I. ricinus is an important vector for tick-borne diseases in Europe [81]. I. ricinus have been collected in the larval, nymphal, and adult stages in Austria [82].…”
Section: Vectors For Bartonella Speciesmentioning
confidence: 99%